2020
DOI: 10.1021/acs.biochem.0c00553
|View full text |Cite
|
Sign up to set email alerts
|

The Cleavage Profile of Protein Substrates by ClpXP Reveals Deliberate Starts and Pauses

Abstract: Cells rely on protein degradation by AAA+ proteases. A well-known example is the hexameric ClpX unfoldase, which captures ATP hydrolysis to feed substrates into the oligomeric ClpP peptidase. Recent studies show that an asymmetric ClpX spiral cycles protein translocation upon ATP hydrolysis. However, how this cycle affects peptide products is less explored in part because ClpP cleavage is thought to be solely defined by sequence constraints. Here, we comprehensively characterize peptides from Caulobacter cresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…7 In fact, it was later discovered that proteolysis by ClpP protease (from Caulobacter crescentus) complexed with ClpX (an unfoldase that feeds ClpP) is mainly governed by local context (substrate cleavage occurred after every 10−13 residues) and not dependent on sequence. 8 Upon examination of the cleavage preferences for any protease and its suite of cleaved substrates, it becomes clear that (i) no single peptide sequence can fully account for the cleavage properties observed for a natural protease and (ii) the sequence specificity alone cannot completely account for the selection of substrates that are cleaved. Thus, we hypothesized at the outset of this work that both the sequence and the local context of the substrate cleavage site may be important factors governing recognition by a protease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 In fact, it was later discovered that proteolysis by ClpP protease (from Caulobacter crescentus) complexed with ClpX (an unfoldase that feeds ClpP) is mainly governed by local context (substrate cleavage occurred after every 10−13 residues) and not dependent on sequence. 8 Upon examination of the cleavage preferences for any protease and its suite of cleaved substrates, it becomes clear that (i) no single peptide sequence can fully account for the cleavage properties observed for a natural protease and (ii) the sequence specificity alone cannot completely account for the selection of substrates that are cleaved. Thus, we hypothesized at the outset of this work that both the sequence and the local context of the substrate cleavage site may be important factors governing recognition by a protease.…”
mentioning
confidence: 99%
“…Another example is the family of ClpP proteases (from Escherichia coli , Staphylococcus aureus , and human mitochondria) that favor peptide substrates composed of specific residues at the P3–P1 positions (e.g., natural amino acids preferred by human mitochondria ClpP at P3–P1 positions are F/W-M/T/L-M/L); nonetheless, proteomics studies of these proteases revealed a very weak cleavage preference . In fact, it was later discovered that proteolysis by ClpP protease (from Caulobacter crescentus ) complexed with ClpX (an unfoldase that feeds ClpP) is mainly governed by local context (substrate cleavage occurred after every 10–13 residues) and not dependent on sequence . Upon examination of the cleavage preferences for any protease and its suite of cleaved substrates, it becomes clear that (i) no single peptide sequence can fully account for the cleavage properties observed for a natural protease and (ii) the sequence specificity alone cannot completely account for the selection of substrates that are cleaved.…”
mentioning
confidence: 99%
“…33 To achieve sustained activity, ClpP develops a heterodimer with its partner molecule ClpX, which is usually called a ClpXP complex. 34 ClpX (NCBI GeneID: 10845), a member of the nuclear-encoded AAA+ protein superfamily with 633 amino acid residues in length, is the only known ATPase component for mammalian ClpP. 30 Similar to ClpP, ClpX owns a 56-residue N-terminal MTS that exists as a hexamer under physiological conditions, and binds with ATP to sustain the stability 35 (Figure 2A).…”
Section: Structurementioning
confidence: 99%
“…Due to the lack of ATPase activity, it only hydrolyzes short peptides of six or fewer amino acids 33 . To achieve sustained activity, ClpP develops a heterodimer with its partner molecule ClpX, which is usually called a ClpXP complex 34 . ClpX (NCBI GeneID: 10845), a member of the nuclear‐encoded AAA+ protein superfamily with 633 amino acid residues in length, is the only known ATPase component for mammalian ClpP 30 .…”
Section: Structure and Operating Mode Of Mitochondrial Qc Proteasesmentioning
confidence: 99%
“…A related question is how the peptide products of ClpXP cleavage, which typically range from 5 to 20 residues long [30][31] , exit the degradation chamber following cleavage of a substrate polypeptide? It has been proposed that structural fluctuations at the equatorial ring-ring interface of ClpP create transient gaps or windows that allow product egress 32 .…”
Section: Clpxp Cleavage Of Small Peptides Implies a Pathway For Produ...mentioning
confidence: 99%